2005
DOI: 10.1038/sj.ijir.3901314
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble lipopolymer as a gene carrier to corpus cavernosum

Abstract: Adenovirus or naked plasmid DNA (pDNA) has been used to deliver the therapeutic gene into corpus cavernosum. However, the potential risks of viral vector and inefficiency of naked pDNA have limited their clinical application. In this study, water-soluble lipopolymer (WSLP) was evaluated as a gene carrier to corpus cavernosum. The WSLP/pDNA complex was transfected to smooth muscle cells in vitro. WSLP had high transfection efficiency, which was comparable to poly(ethylenimine) (PEI). In addition, WSLP had much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…pCMV-Luc, the GBP/pCMV-Luc polyplexes (weight ratio: 20, 40, 60 and 80) or the PEI25K/pCMV-Luc polyplex (weight ratio = 1) was injected into the midportion of the corpus cavernosum of the hypercholesterolaemic mice (N = 5 per group), and the needle was left in place for 2 min to allow the gene to diffuse throughout the cavernous space as previously described (Lee et al, 2005). The amount of pCMV-Luc was fixed at 0.5 lg per each polyplex.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…pCMV-Luc, the GBP/pCMV-Luc polyplexes (weight ratio: 20, 40, 60 and 80) or the PEI25K/pCMV-Luc polyplex (weight ratio = 1) was injected into the midportion of the corpus cavernosum of the hypercholesterolaemic mice (N = 5 per group), and the needle was left in place for 2 min to allow the gene to diffuse throughout the cavernous space as previously described (Lee et al, 2005). The amount of pCMV-Luc was fixed at 0.5 lg per each polyplex.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…9 It exists in either branched or linear forms and has undergone many modifications by various investigators to increase solubility, half-life, cellular uptake and nuclear delivery while decreasing cytotoxicity. 10,11 The optimal formulation for a given application appears to be dependent on the specific target tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this polymer has been used to deliver genes to several different cancers, myocardium and corpus cavernosum. [45][46][47][48][49] In summary, we have demonstrated that ischemiainducible VEGF gene therapy improves the efficacy of VEGF gene therapy for myocardial infarction through decreased apoptosis and increased angiogenesis.…”
Section: Ischemia-inducible Gene Therapy Jw Yockman Et Almentioning
confidence: 89%